KELOLA REFERENSI DENGAN CERDAS: PELATIHAN MENDELEY UNTUK MENINGKATKAN KUALITAS SITASI DAN KARYA ILMIAH MAHASISWA DI STIQ KEPULAUAN RIAU - Nurhayati; Sufyan Muttaqin; Mukhammad; Kamarul Zaman; Muhith; Zaitun Abidin; Asmarika; Fahrina Yustiasari Liriwati; Armizi (DEVELOPMENT: Journal of Community Engagement, 2026)
This study aims to improve students’ ability in managing references and academic citations through training on Mendeley at STIQ Kepulauan Riau. The method employed a community service based training approach using a descriptive quantitative design combined with qualitative analysis. The program was conducted through preparation, implementation, and evaluation stages, involving students as participants. Data were collected using pre-test and post-test assessments as well as observations of participants’ technical skills in using the application. The results indicate a significant improvement in students’ competencies, with the average score increasing from 55.0 in the pre-test to 87.5 in the post-test. The N-Gain value of 0.72 falls into the high category, indicating that the training was effective in enhancing reference management and academic citation skills. The greatest improvement was observed in technical skills, while conceptual understanding of citation showed moderate improvement. These findings suggest that technology-based training effectively improves the quality of students’ academic writing, particularly in citation consistency and bibliography structure.